The effect of dietary tryptophan supplementation, and an oral tryptophan challenge, on urinary excretion of 5-hydroxyindoleacetic acid in domestic dogs - Cheung, Chloe; Rigling, Jess; Stang, Bernadette; Ruaux, Craig (Frontiers in Veterinary Science, 2025)
Chronic enteropathies, commonly referred to as inflammatory bowel disease, are multi-factorial disorders that affect a substantial proportion of both the human population and companion animals. There is an emerging body of evidence suggesting that alterations in serotonin metabolism may contribute to the development of inflammatory bowel disease in humans. 5-Hydroxyindole acetic acid (5-HIAA) is a major metabolite of serotonin which undergoes renal excretion, providing a non-invasive indicator of serotonin metabolism. This study validated a commercial ELISA assay for 5-HIAA for use in canines and investigated the effect of dietary tryptophan supplementation and tryptophan challenge on the excretion of 5-HIAA in healthy dogs (n = 14). Dietary supplementation was associated with sustained alterations in serotonin metabolism, whereas a short-term oral tryptophan challenge, did not significantly impact immediate 5-HIAA excretion at 4- and 8-h post-challenge. These findings provide key insights regarding potential confounding factors for the interpretation of urinary 5-HIAA secretion as a marker of serotonin metabolism in domestic animals. Future prospective studies with a larger sample size are required to compare the serotonin concentrations between dogs with chronic enteropathy and healthy dogs on the tryptophan loading/challenge tests.